Kebijakan Pariwisata Pascapandemi: Analisis Penerapan Agile Governance dalam Mengembangkan Komunitas Wisata Candi Borobudur - Winata, Tirta Pandu; Wulan, Dewi Ontro; Farhaturrahmah, Tazkia Athala (Politicos: Jurnal Politik Dan Pemerintahan, 2023)
The Covid-19 pandemic that hit the world from 2020 to 2022 has significantly impacted various sectors, especially the tourism sector. Borobudur Temple became one of the tourist attractions that experienced a significant decrease in tourist visits during the pandemic. But in 2023, the pandemic status was officially lifted and marked the start of the post-pandemic era. This era is projected to bring significant changes to the tourism sector due to increased mobilization carried out by the community. So, it is necessary to apply the concept of agile governance by everyone involved to give birth to agile and innovative governance. This study uses a qualitative method with a descriptive approach. This study's results indicate a phenomenon arising from the application of agile governance in developing the local community of Borobudur Temple. First, there is an improvement in governance through the development of regional information systems, the construction of business-oriented community facilities, efforts to open up community participation in tourism management, and a quick solution orientation to overcome problems.